Diagnostic significance of hsa_circ_0000146 and hsa_circ_0000072 biomarkers for diabetic kidney disease in patients with type 2 diabetes mellitus - A Fahim, Sally; Badr, Amul; Elkholy, Omayma; Said, Mona; El-Khatib, Mohamed; Sabry, Dina; Gaber, Radwa (Journal of Medical Biochemistry, 2022)
Background: Diabetic Kidney Disease (DKD) is a significant challenge in healthcare. However, there are currently no reliable biomarkers for renal impairment diagnosis, prognosis, or staging in DKD patients. CircRNAs and microRNAs have emerged as noninvasive and efficient biomarkers. Methods: We explored Cannabinoid receptor 1 (CNR1), C reactive protein (CRP), hsa_circ_ 0000146 and 0000072, and hsa-miR-21, and 495 as diagnostic biomarkers in DKD. The serum concentrations of CRP and CNR1 were measured using ELISA. Rt-qPCR was used to evaluate the expression levels of CNR1, circRNAs, and miRNAs in 55 controls, 55 type 2 diabetes mellitus patients, and 55 DKD patients. Their diagnostic value was determined by their ROC curve. KEGG pathway was used to predict the functional mechanism of the circRNA’s target genes. Results: DKD patients exhibited a significant increase in CRP and CNR1 levels, as well as the expression of miR-21 and 495. The expression levels of circ_0000146 and 0000072 decreased in DKD patients. ROC analysis revealed that circRNAs and miRNAs alone or along with CNR1 and CRP have a significant diagnostic potential. The functional prediction results showed the involvement of hsa_circ_0000146 and 0000072 in various pathways that regulates DKD. Conclusion: Therefore, the examined circRNAs and miRNAs may represent a novel noninvasive biomarker for diagnosing and staging DKD.